Neopythagoreanism in the work of Johannes Kepler (2016)
In this article I argue that the methodology in the Johannes Kepler's work is guided by two principles of Pythagorean nature, they are: (i) sameness is made known by sameness, and (ii) harmony arises from establishing a limit to what is unlimited. By way of hypothesis, I present a general outline, which includes those principles, and I indicate how they are present in Kepler's investigations. I examine two particular cases in the light of that schema.